The Existence of Wasathiyyah Islam in Madura (An Analysis of Urban Society’s Acceptance of Islamic Content on Social Media) - Moh. Zahid; Mohammad Hasan (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2018)
The spreading Islamic content through Whatsapp as one of popular social media platforms which no longer reflects moderate (wasatiyyah) Islamic teaching has began to appear. It ranges from the content of Islamic teaching, the pattern of movement, response on contemporary life, to discussion on political system and discourses on nation-state. In responding to the Islamic contents implying radicalism, terrorism and ambition to change the form of state from republic into khilafah based system, most of Maduresse urban people reject it. However, they still rely on the content spreaded through social media in understanding Islam. This dynamics could possibly influence people and lead them to either right or left extreme points out of the frame of moderate Islam taught by Rasulullah pbuh and classically recognized scholars (ulama’ salaf al-salih). Therefore, it is urgent to formulate a preaching strategy with the good content to provide people access on balanced information so they could be selective in understanding Islamic teaching. (Penyebaran konten keislaman melalui media sosial (WhatsApp) yang tidak lagi mencerminkan wasathiyyat al-Islm (moderasi ajaran Islam) mulai bermunculan baik materi keislaman, pola gerakan, penyikapan terhadap kondisi kekinian, bahkan perbincangan system politik dan kehidupan bernegara. Dalam menyikapi konten keislaman yang mengarah pada paham radikalisme, terorisme, dan gagasan mengubah system bernegara NKRI dengan konsep khilafah, mayoritas masyarakat perkotaan di Madura menolaknya. Namun demikian terhadap konten materi keislaman yang disebarkan melalui media sosial, sejumlah kalangan sudah menjadikannya sebagai pijakan dalam memahami Islam. Dinamika ini dapat mempengaruhi masyarakat pada sikap ektrem kanan atau ekstrem kiri, yang keluar dari bingkai Islm wasathiyyat sebagaimana yang diajarkan oleh Rasulullah Saw. dan Para Ulama Salafus Shlih. Oleh karena itu perlu strategi dakwah dengan materi yang tepat agar masyarakat mendapatkan informasi yang berimbang sehingga bisa selektif dalam memahami ajaran Islam)